Emotional Competences and Trait-State Anxiety in University Students in the Context of the Covid 19 Pandemic, Chincha 2021 - Pachas, Milly Soledad Quispe; García, Teresa del Pilar García (Migration Letters, 2024)
The research outlined as a general objective, to determine the relationship between emotional competencies and their components (emotional awareness, emotional regulation, emotional autonomy, social competence and competencies for life and well-being) with trait-state anxiety in university students in the context of the Covid 19 pandemic, Chincha 2021. The research was of basic type, of correlational descriptive level, with analytical method, and hypothetical-deductive and non- experimental design. The population consisted of 200 students, selected with the probabilistic technique, with simple random probability sampling. For data collection, the survey technique was used, and as an instrument: the Adult Emotional Development Questionnaire (QDE-A) of Bisquerra (2018) and the inventory of trait- state anxiety (IDARE) Carranza and Elorreaga, (2019). The results showed that: 48% of respondents have high emotional competencies and no anxiety-state trait. On the other hand, 50% have high emotional competencies and mild trait-state anxiety, 2% have high emotional competence and moderate trait-state anxiety. It is concluded, the Spearman Correlation test, it was possible to determine a mean negative correlation between the variables emotional competencies and trait-state anxiety, finding an association of -.303 with a value calculated for p = 0.000, which is lower than the significance value = 0.05; this is indicative of a strong negative association or mean inverse, among the variables emotional competencies and trait-state anxiety in university students in the context of the Covid 19 pandemic, Chincha 2021.